Biofilm Formation by Salmonella Enteritidis at Different Incubation Temperatures - Rodrigues, Laura Beatriz; Webber, Bruna; Levandowski, Rafael; Gehlen, Sarah Souza; Ruschel dos Santos, Luciana; Pilotto, Fernando; Tondo, Eduardo Cesar; do Nascimento, Vladimir Pinheiro (Acta Scientiae Veterinariae, 2019)
Background: The genus Salmonella, associated with poultry products, is considered the leading cause of foodborne outbreaks in humans in many countries. In Brazil, Salmonella Enteritidis (SE) is the serovar remains as one most frequently isolated from humans, and it is also a major serovar found in animals, food, animal feed, and environmental samples, despite all the efforts to control this pathogen. Also, the bacterium is able to form biofilms on different surfaces, protecting cells from both cleaning and sanitizing procedures in the food industries. This study aimed to verify the ability of Salmonella Enteritidis isolates to form biofilm on polystyrene at different incubation temperatures. Materials, Methods & Results: A total of 171 SE samples were isolated from foodborne outbreaks (foods and stool cultures) and poultry products between 2003 and 2010. The biofilm-forming ability of samples was measured at four different temperatures (3°C, 9ºC, 25ºC, and 36ºC), for 24 h, simulating temperatures usually found in poultry slaughterhouses. Later, 200 μL of each bacterial suspension was inoculated, in triplicate, onto 96-well, flat-bottomed sterile polystyrene microtiter plates, washed, after that, the biofilm was fixed with methanol. The plates were dried at ambient temperature, stained with 2% Hucker’s crystal violet. Afterwards, absorbance was read using an ELISA plate reader and the optical density (OD) of each isolate was obtained by the arithmetic mean of the absorbance of three wells and this value was compared with the mean absorbance of negative controls (ODnc). The following classification was used for the determination of biofilm formation: no biofilm production, weak biofilm production, moderate biofilm production and strong biofilm production. Results demonstrated all isolates from stool cultures and foods involved in foodborne outbreaks, at least one of the four temperatures tested, were able to form biofilm, even at 3°C, undescribed as possible for the growth of SE. SE strains from poultry products also formed biofilm at least at one of the temperatures. Discussion: the prevention of biofilms formation is very important, once they can be difficult to remove from utensils and food equipment surfaces, becoming a chronic source of microbial contamination of foods, possible dissemination of diseases, and increase of resistance to cleaning and sanitization procedures. A high ability for biofilm formation on plastic surfaces was observed. We may consider that Salmonella has the capacity to bind to surfaces, with relevant impacts on public health. Although biofilm formation could be affected by temperature, most of the SE isolates analyzed in our study were strong biofilm producers at all temperatures, including at 3°C, a temperature used for food preservation and until then not acknowledged as worrisome regarding the development of Salmonella spp. There is a common sense that maintenance of food at low temperatures, particularly below 5°C, is safer to consumers as low temperatures reduce microbial multiplication. However, our results show that the growth of SE in its sessile form is possible under refrigeration. These findings lead to the assumption that the ability of SE to form biofilms, especially at low temperatures, is related to its endurance in inhospitable environments, eventually infecting humans, and that may be one of the factors associated with the high prevalence of this serovar in outbreaks of foodborne diseases. To our knowledge, this is the first publication about biofilm formation by Salmonella Enteritidis at 3ºC.